Desain Sistem Pemantau Konsumsi Energi untuk Rusunawa di Indonesia - Yakub Fahim Luckyarno; Sentagi Sesotya Utami; Faridah Faridah; Ressy Jaya Yanti (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2019)
Electricity consumption in the household sector is classified into two categories based on the economic class of the household. The first category is the low class, in which the greatest electricity consumption (approximately 20.00%) is used for lighting. The second category is the medium and high class, in which the greatest electricity consumption (approximately 20.00-32.00%) occurs for powering the air conditioning (AC) system. To date, vertical type housing can be commonly found in the medium class, and as of 2017, the level of occupation has reached 9.52%. This condition calls for an analysis on the energy consumption and energy efficiency of the buildings. Case found in a low-cost apartment building, also known as Rumah Susun Sederhana Sewa (Rusunawa) in Yogyakarta, Indonesia, is one example where an energy monitoring system is needed. This is due to the inhabitants' habit of electrical usage that is unsuitable to the Rusunawa's function, such as their inefficient use of AC and washing machines. The energy meter system measures the electrical voltage and current of electrical appliances that are attached to the system. This system utilizes a ZMPT101B-5 sensor to measure the voltage and an ACS712 sensor to measure the elctrical current. The design of the energy meter system enables one to measure the voltage and current of electrical appliances with a 4.40% margin of error. Based on the measurements obtained in this paper, the AC is the greatest source of power consumption, with an approximate value of 800 kWh.